Insertion of One-third Tubular Plate for Hemiepiphysiodesis in Children : Surgical Technique - Mohd Anuar Ramdhan, Ibrahim; Paul Tan, Boon King; Faris Indra Prahasta, Didi Indra (Texila International Journal of Academic Research, 2023)
Limb length discrepancy and angular deformities are among the main issues in paediatric patients. There are various ways to manage these two problems which includes growth modulation with eight-Plate. For certain reasons, the use of the eight-Plate is limited, thus conventional plates have been selected for the guided growth, for example two-hole one-third tubular plate or reconstruction plate. Literatures reported good results on its use but none of them explained the surgical technique in details. Therefore, we proposed the surgical technique of inserting the two-hole one-third tubular plate in hemiepiphysiodesis in children, which includes pre-skin incision preparation, placement of one-third tubular plate and screw insertion. The three steps are surgeon-friendly and less demanding, being suitable to apply to paediatric patients that require growth modulation